2018
DOI: 10.1002/bmc.4421
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolism of the eight main bioactive ingredients of gegen qinlian decoction by the intestinal flora of diarrhoeal and healthy piglets

Abstract: Diarrhoeal diseases alter the composition of intestinal flora, thereby affecting the efficacy of herbal medicinal formulations. Gegen Qinlian decoction (GQD), a Chinese traditional herbal formulation, is widely used to treat infectious diarrhoea. However, little is known about the microbial disposition of GQD in the diarrhoeal state. In this study, the comparative metabolism of components of GQD by diarrhoeal and normal intestinal flora was investigated in vitro. UPLC-MS/MS was performed for simultaneous analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The ingredients analysis demonstrated that GQD is primarily composed of antibacterial agents (Liu et al, 2018), which indicates that GQD attenuates diarrheal symptoms by promoting the destruction of pathogenic microorganisms. Recently, a clinical study that treated patients with type 2 diabetes with GQD for 12 weeks found that GQD features hypoglycemic efficacy (Xu J. et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The ingredients analysis demonstrated that GQD is primarily composed of antibacterial agents (Liu et al, 2018), which indicates that GQD attenuates diarrheal symptoms by promoting the destruction of pathogenic microorganisms. Recently, a clinical study that treated patients with type 2 diabetes with GQD for 12 weeks found that GQD features hypoglycemic efficacy (Xu J. et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, gut microbiota is known for its direct and indirect effects on drug and xenobiotic metabolism (Wilson and Nicholson, 2017). The intestinal flora mediates the metabolism of GQD constituents, including daidzin, genistin, and liquiritin via beta-glucosidase; baicalin, wogonoside, and glycyrrhizin via beta-glucuronidase; and berberine and coptisine via nitroreductase (Liu et al, 2019a).…”
Section: Pharmacokinetics Absorptionmentioning
confidence: 99%
“…Drugs with oral administration can promote the host metabolism and modulate the structure of gut microbiota ( 58 ). In term, the gut microbiota could mediate the metabolism of bioactive constituents in oral drugs via various targets ( 59 ). Previous studies further provided the reliable and direct evidence for the additive and synergistic effects of CHFs and metformin on modulating gut microbiota and ameliorating metabolic disorders in type 2 diabetic patients ( 60 62 ).…”
Section: Discussionmentioning
confidence: 99%